Artificial Intelligence Revolution in Interior Design - Bunkheila, Mohammed (Libyan International Medical University-Faculty of Information Technology, 2022)
The Artificial Intelligence idea is a big change in our era for all of different work fields around the world, such as (technology, medicine, engineering, social media, smartphones, manufacturing, assistants, business and advertisement, etc.,). The main idea of this research is about Artificial Intelligence Improvement and changes, designers replacing, and assistance in Interior Design